Association between maternal age and postpartum depression in Ardabil, Northwest of Iran: a cross-sectional study - Afrouz Mardi; Sara Mahdad; Mehrnaz Mashoufi; Samira Shahbazzadeghan; Atefeh Shadman (Patient Safety and Quality Improvement Journal)
Introduction: Postpartum depression (PPD) is a mood disorder that negatively affects mother, child and family. This study aims to examine the association between maternal age and postpartum depression. Materials and Methods:This cross-sectional descriptive study involved 200 women referred to the Ardabil health care centers for postpartum care six weeks after delivery from May to December 2020. Cluster sampling was done, and participants were stratified according to <19 years and ≥ 19 years. Data were collected using the Edinburgh postpartum depression scale. Associations with depression were analyzed via logistic regressions were used to compare the prevalence of depression among two groups. Results:Eight percent of the adult participants aged ≥ 19 years experienced PPD compared to 4% of the Adolescent participants aged < 19 years, while the overall prevalence was 6%.  Adult Participants (≥ 19 years) compared to adolescents (< 19 years) had higher formal education, were more likely to be employed, had a greater number of pregnancies (gravida), were of greater maternal age, and their spouses were older (p<0.01). Significant relationships were found between PPD and gravida (p=0.011) and husband employment status (P=0.031) in participants ≥19 years. However, no significant relationships were found between PPD and independent variables for participants < 19 years. Conclusion:The prevalence of PPD appears to be relatively low in women from the Northwest of Iran. In women >19 years, PPD appears to be associated with gravida and spouse’s employment status.